Can heart rate variability demonstrate the effects and the levels of mindfulness? A repeated-measures study on experienced and novice mindfulness practitioners - Yanping Wei; Yifei Xu; Wanlin Chen; Jing Zheng; Hang Chen; Shulin Chen (BMC Complementary Medicine and Therapies)
Abstract Background Heart rate variability (HRV) is a potential biomarker that might demonstrate the effects of mindfulness, but it might be influenced by practice experiences. This study wanted to elucidate the possibility of using HRV metrics to reveal the effects of mindfulness and examine its variation between novice and experienced mindfulness practitioners. Methods Forty-six participants (20 experienced practitioners, 26 novices) were enrolled to practice 14-day mindfulness training. HRV data were collected during three phases (20 min baseline, T1; 20 min mindfulness, T2; 20 min post-mindfulness, T3) using Holter monitoring. The linear mixed model was conducted to explore the effects of group and time based on standardized data. Results The experienced group had higher full-scale scores of FFMQ both in the pre-test (t = -3.34, df = 44, p = 0.002) and the post-test (t = -2.35, df = 44, p = 0.025). Both groups showed significant changes in HRV indices (e.g., RMSSD, SDNN, LnHF) from T1 to T2 or T3 (p < 0.05). In the experienced group, significant fluctuations (p < 0.05) were observed at T2, followed by recovery at T3, in SD1/SD2, Sample Entropy, normalized High Frequency (HFn), DFA_α1, and DFA_α2. In contrast, the novice participants only showed monotonic changes in SD1/SD2 and DFA_α1. Conclusions This study revealed significant HRV changes during mindfulness practice, with distinct patterns observed between novice and experienced practitioners.